Designing a Sustainable Pedal-Powered Washing Machine for Rural Areas - S. A. Ladkat; Dnyanesh R. Kende; Adesh S. Gore; Aditya S. Gosavi; Athrava R. Gulave (International Journal of Manufacturing and Production Engineering, 2023)
The ingenuity can be found in its simple construction, sparse use of pricey components, extremely low upkeep and repair costs, accessibility to all segments of society, and lack of environmental impact. According to the environmental issue, it is essential to use energy in alternative ways in order to conserve it. The PPWM additionally conserves time, water in a container and power while being reasonably priced. The leg-powered washing machine (PPWM) is a fantastic invention all of it's own; it evolved specifically to be used for washing clothes by pressing a pedal.. PPWM is made of easily & readily available scrap components of washing machine & bicycle, In PPWM bicycle assembly is used as frame & power transmission unit and this assembly is welded to a prefabricated assembly of washing machine drum which also consists of bevel gear mesh arrangement. It is an equipment that transfers human peddling action into the rotational motion of the wheel; the present project is an attempt for a concept for a fabric washing machine that can match the criteria. Despite the machine's driving motor differs in comparison to that of other akin machines, this concept's basic principle is identical as well. In the moment's effort, given the job's limits, the goal of minimising the starting cost and running cost of machine washing is virtually realized. The primary objective is to minimize the amount of labor required to give light washing in isolated, gloomy places that are far from construction and power.
Keywords: Bevel Gear; Chain; Pedal; Pedal powered washing machine (PPWM); sustainable